The Diversity of Knowledge Concerning Geographical Areas Based on Surveys Conducted in Institutions of Primary Education in Hungary - Lupfer-Juhász, Eszter (Ethnographica et Folkloristica Carpathica, 2023)
My study will discuss the Hungarian public education system, more specifically, the knowledge about and the measurement of the concept of geographical areas as they appear in the subject Hon- és népismeret [approximately: Our Homeland and Its People(s)] in the Hungarian primary education system. The cultural landscape formed by human activity is an important part of Hon- és népismeret education, which also includes knowledge of spatiality, ethnographic geographical areas and maps. In my research, I was interested what students taking Hon- és népismeret courses think and know about geographical areas; moreover, if they can use maps and place major Hungarian and ethnographic geographical areas (provinces) on blind maps. In my search, I have conducted a survey among students learning Hon- és népismeret in primary schools in Debrecen with the aim of measuring their knowledge of geographical areas and ethnographic geographical areas, especially related to the use of maps. So, in my study, I present all the tasks of the survey and the students’ answers. Furthermore, I describe the method used during the survey and the data processing.